Hematopoietic stem cell transplantation in pediatric patients with acute myeloid leukemia without favorable cytogenetics. (1st August 2017) - Suh, Jin Kyung; Lee, Seong Wook; Koh, Kyung‐Nam; Im, Ho Joon; Choi, Eun Seok; Jang, Seongsoo; Park, Chan‐Jeoung; Seo, Jong Jin
Abstract: Intensified chemotherapy, HSCT, and supportive care improve the survival of pediatric patients with AML. However, no consensus has been reached regarding the role of HSCT in patients without favorable cytogenetics. We evaluated OS and EFS according to prognostic factors that affect clinical outcomes, including cytogenetics risk group, conditioning regimen, donor type, disease status at the time of HSCT, and number of chemotherapy cycles prior to HSCT in 65 pediatric patients with AML without favorable cytogenetics who underwent HSCT. Fifteen of the 65 patients died: three of TRM and 12 of disease‐related mortality. The 5‐year OS and EFS were 78.0% and 72.0%, respectively, and the 5‐year cumulative relapse and TRM rates were 26.9% and 5.1%, respectively. Survival rates were not influenced by cytogenetic group (intermediated vs. poor), donor type (related vs. unrelated), transplant type (myeloablative vs. reduced‐intensity conditioning), or number of pretransplant chemotherapy cycles (≤3 vs. >3 cycles). The low TRM rate and encouraging outcomes suggest that HSCT may be a feasible treatment for pediatric patients with AML without favorable cytogenetics.